Urban solid waste and the 2030 Agenda: An analysis of actions taken by the municipality of São José do Seridó/RN (Research, Society and Development, 2021)
The actions carried out by the municipal entity of São José do Seridó/RN, regarding the management of solid waste in the municipality and its correlation with the objectives outlined in the 2030 Agenda, prepared and ratified by the signatory countries of the United Nations (UN), comprise the axis of analysis in this paper. For a better understanding of this relation, it was adopted as a general objective to understand the contribution of urban solid waste management actions carried out by the municipality of São José do Seridó/RN, in compliance with the objectives of the UN 2030 Agenda. Once this was done, the theme was developed through the following specific objectives: (i) identifying the actions taken by the municipality to mitigate urban solid waste, (ii) understanding the relevance of the actions taken to mitigate the impact caused by environment and (iii) relating the actions developed to the objectives of the 2030 Agenda. In order to achieve the objectives outlined, an exploratory and descriptive methodology was adopted, with a bibliographic deepening and empirical data collection, through a structured participant research. The analysis of the data from the research follows the qualitative approach. The present study is justified by the fact that urban waste is still a problem with few practical solutions. For this reason, most Brazilian municipalities are unable to fully meet the requirements of the National Solid Waste Policy. Finally, it appears that the municipal entity carries out activities that align commitment and sustainable responsibility, in order to generate less environmental impact, managing to partially meet some SDG.